The Evolution and Trend Analysis of Rural Planning Research Hotspots under the Background of Territorial and Spatial Planning - Zheng, Qixi (Frontiers Research of Architecture and Engineering, 2021)
Under the background of the new round of land and space planning, the research on rural planning in China is undergoing positive changes. Based on the past emphasis on engineering thinking and planning technology, it has entered the field of planning strategy and planning guidance. The extended development trend shows a research trend of intensified integration with public management disciplines and government governance theories. The intervention of government regulation research will provide a solid theoretical guarantee for the rural revitalization strategy that focuses on planning and planning first. In order to study the rural planning hotspots and trends in the context of territorial and spatial planning, using CiteSpace software to map rural areas from the perspectives of the number of articles, authors, publishing organizations, keyword co-occurrence networks, keyword clustering analysis, hotspot evolution, prominent word analysis, etc. The knowledge map was planned and visualized comparative analysis was carried out.